Length–weight relationships for estuarine fishes in subtropical estuary - Carvalho, Barbara Maichak de; Bot, Renato; Spach, Henry Louis (Acta Scientiarum. Biological Sciences, 2020)
The present study describes the length/weight ratio (LWR) of 20 fish species caught in an intertidal area of the Paranaguá Estuarine Complex, southern Brazil. Fish were caught with three beach seine nets, with 2m high, 70m long and distance between knots of 2.5; 4 and 5cm. A total of 880 individuals of 21 species belonging to 11 families were captured, ranging from 5 to 75.5cm in total length. All species analyzed are widely distributed throughout the Southwestern Atlantic. Positive allometric growth (b > 3) was predominant, occurring in 60% species, 35% presented negative allometry (b < 3) and only 5% had isometric growth (b = 3). Many factors could be influencing the distinct growth patterns observed between the literature and the present study, such as the environmental influences, the reduced number of specimens, the sampling methods, the sampling periods and the estimation of the LWR with grouped sexes.